ANALISIS KHIYAR MAJLIS DI ERA ONLINE SHOP - Humaidi, M. Rif’an (Universitas Kiai Abdullah Faqih Gresik, 2024)
Abstract: Buying and selling is a type of activity that is often carried out by humans in everyday life. This economic behavior has been formed since humans began to feel the need for other individuals who had goods/services that they did not have even though they needed or wanted them. It is from the development of forms of buying and selling transactions and marketing that we now know the term online shop. The definition of an online shop is a process of purchasing goods or services from those who sell via the internet. Khiy?r Majlis is a voting right owned by the seller and buyer which is always attached to both of them and will not automatically expire unless they or one of them separates from the Majlis Akad. In online transactions, Khiy?r Majlis is difficult to apply, because of the differences in Majlis Akad that occur in online transactions. The purpose of this article is to analyze the new formulation, so that it can apply to online transactions of any type. The results of this research show that the classic Khiy?r Majlis concept is the right to choose for sellers and buyers to continue transactions that have been realized or cancel them in the same meeting. Conventional Khiy?r Majlis does not find a point of relevance when applied to online shops, because online shops are very different from Conventional buying and selling is carried out by holding a meeting between the buyer and the seller in the same Majlis. The concept of Khiy?r Majlis in online transactions is directly likened to two people transacting in one place which ends with the internet connection being cut off, while the concept of Khiy?r Majlis in online transactions is not directly after The buyer accepts the agreement after the arrival of the ?j?b written message from the seller. Keywords: Khiyar majlis, Concept, Online shop